Dampak Over Kapasitas Bagi Warga Binaan Pemasyarakatan (WBP) Di Rumah Tahanan Negara Kelas IIB Purbalingga - Kurniawan Abdul Azis; Ikama Dewi Setia Triana; Muhammad Yusril Irza (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2025)
Overcapacity in State Detention Centers (Rutan) is a serious issue in Indonesia's correctional system. This study aims to analyze the impact of overcapacity on Correctional Inmates (WBP) at Class IIB Purbalingga Detention Center and identify efforts to address this problem.This research employs a qualitative method with a normative and empirical juridical approach. Data was collected through interviews with WBP and detention center officers, as well as literature studies and direct observations. The findings indicate that overcapacity at Class IIB Purbalingga Detention Center results in various negative impacts, including deteriorating health conditions due to overcrowding, increased psychological stress leading to conflicts among inmates, and reduced effectiveness of rehabilitation programs. Additionally, limited staff resources lead to suboptimal supervision and services for inmates.Efforts to address overcapacity include assimilation programs, accelerated parole processes, and improvements to detention center facilities. However, challenges remain, such as high recidivism rates and the limited implementation of alternative sentencing policies. Therefore, comprehensive policy reforms are needed, including the application of restorative justice concepts to reduce inmate populations and enhance the quality of Indonesia's correctional system.